Promoting and protecting minority languages in Zimbabwe: use of the 1992 UN Minorities Declaration - Dziva, Cowen; Dube, Brian (Brill Academic Publishers, 2016)
Zimbabwe in 2012 joined the rest of the world to celebrate the 20th anniversary of the unanimously adopted United Nations Declaration for Minorities in 1992, as the main document granting non-dominant groups protection by states in all spheres of life. For most African states, Zimbabwe included, the Declaration came amidst ubiquitous marginalisation and disavowal of minority languages in favour of foreign and dominant tongues. Unsurprisingly, Article 4(3(4) of the Declaration sought to obviate this status quo through calling on states to ensure that minorities learn and use their mother languages for development. Ever since the Declaration, the use of minority languages in public spheres has become a hotly debated subject in democratic societies, with many linguists deciphering minority languages to be one of the missing links to Africa’s development. The aim of this article is, therefore, to encapsulates the good practices by Zimbabwean stakeholders and prospects in implementing minority languages. After scrutinising national policies and efforts to advance minority languages, it can be seen that though discernible it is still a long way for Zimbabwe to close the gap on the ideals of the 1992 Declaration. As such, Zimbabwe is propelled to move beyond mere ratification and take concrete steps towards implementation through translating national documents into minority tongues, revamping the education curriculum, public awareness campaigns on the Declaration, training lexicographers, minority sensitive budgeting and constitutionalism if they are to fulfil their obligations under the Declaration.